Free phase gas processes in a northern peatland inferred from autonomous field‐scale resistivity imaging. Issue 4 (21st April 2016) - Terry, Neil; Slater, Lee; Comas, Xavier; Reeve, Andrew S.; Schäfer, Karina V. R.; Yu, Zhongjie
Abstract: The mechanisms that control free phase gas (FPG) dynamics within peatlands, and therefore estimates of past, present, and future gas fluxes to the atmosphere remain unclear. Electrical resistivity imaging (ERI) is capable of autonomously collecting three‐dimensional data on the centimeter to tens of meter scale and thus provides a unique opportunity to observe FPG dynamics in situ. We collected 127 3‐D ERI data sets as well as water level, soil temperature, atmospheric pressure, and limited methane flux data at a site in a northern peatland over the period July–August 2013 to improve the understanding of mechanisms controlling gas releases at a hitherto uncaptured field scale. Our results show the ability of ERI to image the spatial distribution of gas accumulation and infer dynamics of gas migration through the peat column at high (i.e., hourly) temporal resolution. Furthermore, the method provides insights into the role of certain mechanisms previously associated with the triggering of FPG releases such as drops in atmospheric pressure. During these events, buoyancy‐driven gas release primarily occurs in shallow peat as proposed by the "shallow peat model." Releases from the deeper peat are impeded by confining layers, and we observed a large loss of FPG in deep peat that may likely represent a rupture event, where accumulated FPG escaped the confining layer as suggested by the "deep peat model." Negative linear correlations between water table elevation and resistivity result from hydrostatic pressure regulating bubble volume, although these variations did not appear to trigger FPG transfer or release. Key Points: Field‐scale autonomous resistivity imaging is used to infer gas content changes in peat Pressure decreases cause bubble expansion and rapid drops trigger ebullition Findings support shallow and deep peat models in terms of biogenic gas release from peat soils